Removal of Expression of Concern for ‘Lipid-lowering therapy in patients with coronary heart disease: an Italian real-life survey. Results from the Survey on Risk FactOrs and CardiovascuLar secondary prevention and drug strategieS (SOFOCLES) in Italy’ - The Monaldi Archives for Chest Disease Editors (Monaldi Archives for Chest Disease)
Removal of Expression of Concern for ‘Lipid-lowering therapy in patients with coronary heart disease: an Italian real-life survey. Results from the Survey on Risk FactOrs and CardiovascuLar secondary prevention and drug strategieS (SOFOCLES) in Italy’ by Caterina Oriana Aragona et al., Monaldi Arch Chest Dis, 2024, Accepted Manuscript, https://doi.org/10.4081/monaldi.2024.2972 IF: 1.1 Q4 NA